Changes in Lower Extremity Muscle Quantity and Quality in Patients with Subacute Stroke - Da Hye Kim; Eun Sol Cho; Young Sook Park; Hyun Jung Chang; Jin Gee Park; Jae Yeon Kim; Jeong Hwan Lee (Annals of Rehabilitation Medicine, 2023)
Objective To analyze the changes in muscle mass and quality with time on the paretic and non-paretic sides in subacute stroke patients and identify correlations between the variation of muscle mass and quality and lower limb functions. Methods Thirty hemiplegia patients diagnosed with stroke participated in this study. To evaluate poststroke muscle changes, longitudinal measurement of muscle mass and quality was conducted with bilateral lower limbs. The elastic shear modulus was measured using shear wave elastography and muscle thickness (MT) of rectus femoris, vastus intermedius, vastus lateralis (VL), vastus medialis, tibialis anterior, and gastrocnemius (GCM) muscles. Functional evaluation was performed using Berg Balance Scale (BBS), Five Times Sit to Stand Test (FTSST). Follow-up was performed at discharge. The muscle mass and quality were compared according to time. We analyzed whether muscle quantity and quality were related to function. Results MT demonstrated no significant change with time. The elastic shear modulus increased significantly in the paretic VL and GCM muscles and did not change significantly in the muscles on the non-paretic side. Correlation analysis detected that elastic shear modulus in the VL has a cross-sectional negative relationship between BBS and positive relationship between FTSST. There were significant correlation between variation of FTSST and the variation of the elastic shear modulus in VL. Conclusion Only paretic VL and GCM muscle quality changed in subacute stroke patients and muscle’s property related to lower limb functions. Therefore, the lower extremity requires an approach to muscle quality rather than quantity for subacute stroke patients.